Modeling Chemotherapy Resistant Leukemia In Vitro - Slone, William L. (J Vis Exp, 2016)
It is well established that the bone marrow microenvironment provides a unique site of sanctuary for hematopoietic diseases that both initiate and progress in this site. The model presented in the current report utilizes human primary bone marrow stromal cells and osteoblasts as two representative cell types from the marrow niche that influence tumor cell phenotype. The in vitro co-culture conditions described for human leukemic cells with these primary niche components support the generation of a chemoresistant subpopulation of tumor cells that can be efficiently recovered from culture for analysis by diverse techniques. A strict feeding schedule to prevent nutrient fluxes followed by gel type 10 cross-linked dextran (G10) particles recovery of the population of tumor cells that have migrated beneath the adherent bone marrow stromal cells (BMSC) or osteoblasts (OB) generating a "phase dim" (PD) population of tumor cells, provides a consistent source of purified therapy resistant leukemic cells. This clinically relevant population of tumor cells can be evaluated by standard methods to investigate apoptotic, metabolic, and cell cycle regulatory pathways as well as providing a more rigorous target in which to test novel therapeutic strategies prior to pre-clinical investigations targeted at minimal residual disease.